Pendampingan Belajar Siswa di Kelas dengan Memanfaatkan Media Pembelajaran Powerpoint dan Video Pembelajaran - Nur, Fitriani; Anugra Sukkuru; Baharuddin; Thamrin Tayeb; Andi Ika Prasasti Abrar (Faculty of Tarbiyah and Teacher Training, 2024)
This community service aims to overcome students' understanding difficulties in the material of the Two-Variable Linear Equation System (SPLDV) by utilising power point learning media and learning videos at MTsN Gowa. The method used is learning assistance with a focus on the preparation and implementation of Problem-Based Learning (PBM), using innovative learning media such as power point media and learning videos. The results of this mentoring showed that the use of innovative learning media, such as power points and learning videos, succeeded in creating an interesting learning environment and supporting student learning success. Despite facing the obstacles of curriculum differences and student comprehension difficulties, the innovative measures succeeded in improving student understanding from block to block, with satisfactory results in the last block. Evaluation was conducted through learning outcome tests. The results of this service show that mentoring using power point learning media and learning videos successfully overcomes the obstacles that arise, and significantly improves student learning outcomes. This mentoring contributes to practical understanding and teaching strategies that can be applied in modern educational contexts.